Locating data use in the microprocesses of district-level deliberations - Alice Huguet; Anna-Ruth Allen; Cynthia E. Coburn; Caitlin C. Farrell; Debbie H. Kim; William R. Penuel (Taylor & Francis Group, 2017)
While there is an abundance of data-use literature available, there is still a need to develop methodological approaches for studying naturally occurring data use in decision-making processes over time. The central contribution of this paper is a strategy to understand the use of data in long-term observations of educational leaders' policy-making deliberations. Using longitudinal and observational data, we created 'decision trajectories' that traced microprocesses of deliberation around specific decisions over time. We employed frame theory to locate when and how data entered decision-making processes within these trajectories. Our approach addresses the use of data as they arise in the context of longitudinal observations - a method that provides insight into how data may be used to inform, frame, or justify educational decisions.